singular and general solution
e^3x(p-1)+p^3e^2y=0;X=e^x ,Y=e^y by substitution
"e^y(1-p)=p^3e^{3(y-x)}"
Use the substitution "X=e^x, Y=e^y"
"\\dfrac{dy}{dx}=\\dfrac{e^x}{e^y}\\cdot\\dfrac{dY}{dX}=>p=\\dfrac{X}{Y}\\cdot\\dfrac{dY}{dX}"
"Y(1-\\dfrac{X}{Y}\\cdot\\dfrac{dY}{dX})=(\\dfrac{X}{Y}\\cdot\\dfrac{dY}{dX}\\cdot\\dfrac{Y}{X})^3"
"Y-X\\dfrac{dY}{dX}=(\\dfrac{dY}{dX})^3"
The Clairaut equation
"Y=XP+P^3, P=\\dfrac{dY}{dX}"Differentiating in "X," we have
"dY=XdP+PdX+3P^2dP"
Replace "dY" with "PdX" to obtain:
"dP(X+3P^2)=0"
By equating the first factor to zero, we have
Now we substitute this into the differential equation.
The general solution is given by
By equating the second term to zero we find that
This gives us the singular solution of the differential equation in parametric form:
"Y=XP+P^3"
By eliminating "P" from this system, we get the equation of the integral curve:
Since "X=e^x, Y=e^y," then the singular solution of the differential equation does not exist.
The general solution is given by
Comments
Leave a comment